2006
DOI: 10.1007/s00436-006-0248-2
|View full text |Cite
|
Sign up to set email alerts
|

Red and transparent brine shrimps (Artemia parthenogenetica): a comparative study of their cestode infections

Abstract: Although the red colour of brine shrimps has previously been supposed to be associated with cestode parasitism, no evidence has been provided that red and transparent brine shrimps differ in their role for cestode circulation. We compared the cestode infections in 100 red and 100 transparent Artemia parthenogenetica collected from the Odiel salt pans in Spain. Seven cestode species were recorded in red, and only four of them were recorded in transparent brine shrimps. The red brine shrimps were more infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…We found no evidence of regulating effects of parasite infections on the populations of A. franciscana, although these are hard to detect due to the low infection rates (see also Sánchez et al 2012). The lack of parasite-induced control on the host population contrasts strongly with parasite-associated modifications of appearance, behaviour and fecundity in the native Artemia reported previously (Thiéry et al 1990;Amat et al 1991a;Varó et al 2000;Sánchez et al 2006aSánchez et al , 2007Sánchez et al , 2009bSánchez et al , 2012Sánchez et al , 2013Rode et al 2013). Therefore, the differences of parasite burden in native and invasive brine shrimp may result into differential predator-prey outcomes (Sánchez et al 2009a;Dunn et al 2012), i.e.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We found no evidence of regulating effects of parasite infections on the populations of A. franciscana, although these are hard to detect due to the low infection rates (see also Sánchez et al 2012). The lack of parasite-induced control on the host population contrasts strongly with parasite-associated modifications of appearance, behaviour and fecundity in the native Artemia reported previously (Thiéry et al 1990;Amat et al 1991a;Varó et al 2000;Sánchez et al 2006aSánchez et al , 2007Sánchez et al , 2009bSánchez et al , 2012Sánchez et al , 2013Rode et al 2013). Therefore, the differences of parasite burden in native and invasive brine shrimp may result into differential predator-prey outcomes (Sánchez et al 2009a;Dunn et al 2012), i.e.…”
Section: Discussioncontrasting
confidence: 56%
“…Both adult shrimps and metanauplii participate in cestode life cycles (Redón et al 2011). The presence of larval tapeworms (cysticercoids) in the native brine shrimps is associated with modifications of their colouration (Thiéry et al 1990;Amat et al 1991a;Sánchez et al 2006a) and altered surfacing and photophobic behaviour , thus increasing the probability of being *Corresponding author: bbg@ecolab.bas.bg…”
Section: Introductionmentioning
confidence: 99%
“…The red colour associated with modifications of feeding behaviour and carotenoids accumulation make hosts more visible by water birds (Thiéry et al 1990, Amat et al 1991a, Robert and Gabrion 1991, Varó et al 2000, Sánchez et al 2006. Amat et al (1991b) found that the parasitized individuals have a higher lipid level, attain bigger size and live longer than the uninfected ones in order to increase the profitability of the prey, which would be a phenomenon of "favorisation" (Combes 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The latter authors studied the distribution of the parasites in various populations of Artemia from the French salterns and highlighted the role of brine shrimp as intermediate host of cestodes parasitizing flamingos. Amat et al (1991a, b), Varó et al (2000), Georgiev et al (2005Georgiev et al ( , 2007 and Sánchez et al (2006Sánchez et al ( , 2007Sánchez et al ( , 2009) studied cestode parasitism in Spanish Artemia populations and their effect on the behaviour of the intermediate host.…”
Section: Introductionmentioning
confidence: 99%
“…As with trematodes and acanthocephalans, many cestode species alter the behaviour of their intermediate hosts to enhance trophic transmission to final definitive hosts (Amat et al, 1991;Gabrion et al, 1982;Robert and Gabrion, 1991;Sánchez et al, 2006;Sánchez et al, 2007). Recently, a parasito-proteomics study using SELDI-TOF MS was performed in order to compare the head proteome of uninfected individuals of Artemia parthenogenetica (Bowen and Stirling) (Branchiopoda: Anostraca) with that of infected individuals manipulated by one of the three following cestode species: (1) Flamingolepis liguloides (Gervais) (Cestoda, Hymenolepididea) infecting flamingos, (2) Confluaria podicipina (Szymanski) (Cestoda, Hymenolepididea) infecting grebes and (3) Anomotaenia tringae (Burt) (Cestoda, Diphyllidea) infecting shore birds (Sánchez et al, 2009).…”
Section: Artemia-cestode Associationsmentioning
confidence: 99%